Pendampingan Pemanfaatan Teknologi Komputer untuk Digitalisasi Administrasi UMKM - Rahman Peliza (SIGMA : Jurnal Sinergi Mengabdi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the community’s economy; however, many MSME actors still face challenges in managing business administration. Manual record-keeping practices result in poorly organized business data, difficulties in financial monitoring, and obstacles to effective business decision-making. This community service activity aims to improve the capacity of MSME actors in utilizing computer technology to digitalize business administration. The implementation methods include planning, socialization, training on the use of computer applications, assistance in applying digital administration, as well as monitoring and evaluation. The results indicate an increase in MSME actors’ understanding and skills in managing digital business administration, particularly in financial record-keeping, business data management, and preparation of administrative documents. Administrative digitalization has a positive impact on data organization, business management efficiency, and the professionalism of MSME actors. Although challenges remain related to varying levels of digital literacy and consistency in implementation, overall, this activity successfully achieved its intended objectives. This community service program is expected to serve as a model for sustainable MSME digitalization support.